Kesantunan Negatif pada Tuturan Keluhan Anime Naruto Shippuden - Marina Indahningrum; Djodjok Soepardjo; Roni Roni (LP. Ma'arif Janggan Magetan, 2023)
This study aims to analyze politeness in utterances of complaints in Japanese. Complaint utterances are essentially rude speech acts to convey negative feelings that tend to offend the other party's feelings, even so the speaker can consider politeness to maintain harmony in communication between humans. Complaint utterances are examined through sociopragmatics by using the strategy concept of Anna Torsbog's complaint strategy and Brown and Levinso's negative politeness. the first season of Naruto Shippuden anime which is analyzed through the stories told by the characters. The results of the study found that negative politeness pays respect, negative politeness questions, negative politeness is not optimistic.